La evaluación formativa: una ruta para aprendizaje de la resolución de problemas. (2020)
The present work is an investigation of exploratory scope, from a qualitative approach the objective set forth in this is to elaborate a route from the formative evaluation to the learning of the problem-solving competence in the Gabriel Escorcia Gravini Educational Institution. For the formative evaluation, the approaches of Piaron (1988), López (2009), Díaz-Barriga (2002), Dunn and Mulvenon (2009) are addressed, apart from Luna (2015), Conley (2007) and de Domínguez and Espinoza (2019), Poyla (2004) on problem solving. To respond to the objectives, an investigation was proposed within the interpretive paradigm, of a qualitative type, with an action research method, the scope is exploratory since it is a subject or problem of little studied research, of which there are many doubts or has not been addressed before. Among the techniques applied are direct observation, interview and checklist to understand the conception of formative evaluation of teachers and characterize the evaluation instruments implemented in the classroom, to determine the learning of the problem-solving competence. In the end, after elucidating the results, a route is developed from the formative evaluation to ensure the development of the problem solving skills from the steps of a class to think by López (2011) complemented by a series of strategies proposed by the authors Ambrose, Bridges, Di Pietro, Lovett and Norman (2017).